Strategi Orangtua Bekerja dalam Mendukung Anak dengan Speech Delay Pada Usia 5 Tahun - Sarah Salsabilla; Neneng Tasu’ah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to describe the strategies used by working parents in supporting children with speech delay. Using a qualitative approach and in-depth interviews with three families, data were collected on the dynamics and challenges parents face in providing language stimulation. The findings reveal that limited time due to work is a major obstacle; however, parents remain proactive in supporting their children through simple communication, educational media, and involvement of extended family members. Parents also realize the importance of creating a positive environment to make children feel comfortable while communicating. Consistency, patience, and rewarding children's efforts are key to supporting their language development. This research reinforces previous findings that emphasize the crucial role of parents in early childhood language development, especially in cases of speech delay.